2012
DOI: 10.1038/leu.2012.208
|View full text |Cite
|
Sign up to set email alerts
|

Altered miRNA and gene expression in acute myeloid leukemia with complex karyotype identify networks of prognostic relevance

Abstract: Recently, the p53-miR-34a network has been identified to have an important role in tumorigenesis. As in acute myeloid leukemia with complex karyotype (CK-AML) TP53 alterations are the most common known molecular lesion, we further analyzed the p53-miR-34a axis in a large cohort of CK-AML with known TP53 status (TP53 altered , n ¼ 57; TP53 unaltered , n ¼ 31; altered indicates loss and/or mutation of TP53). Profiling microRNA (miRNA) expression delineated TP53 alteration-associated miRNA profiles, and identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
33
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 49 publications
(54 reference statements)
0
33
0
Order By: Relevance
“…In addition, p53 was found to monitor the expression of miR-34a after cisplatin and miR-34a targeted to MYCN to sensitize lung cancer cells to cisplatin [37]. It has been shown that miR-34a was identified as the most significantly highly expressed miRNA among TP53 alteration-associated miRNA profiles in acute myeloid leukemia with complex karyotype (CK-AML) [38]. Besides, low expression of miR-34a and TP53 alterations predicted for chemotherapy resistance and inferior outcome in CK-AML clinically [38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, p53 was found to monitor the expression of miR-34a after cisplatin and miR-34a targeted to MYCN to sensitize lung cancer cells to cisplatin [37]. It has been shown that miR-34a was identified as the most significantly highly expressed miRNA among TP53 alteration-associated miRNA profiles in acute myeloid leukemia with complex karyotype (CK-AML) [38]. Besides, low expression of miR-34a and TP53 alterations predicted for chemotherapy resistance and inferior outcome in CK-AML clinically [38].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that miR-34a was identified as the most significantly highly expressed miRNA among TP53 alteration-associated miRNA profiles in acute myeloid leukemia with complex karyotype (CK-AML) [38]. Besides, low expression of miR-34a and TP53 alterations predicted for chemotherapy resistance and inferior outcome in CK-AML clinically [38]. However, it was reported that HL-60 cells did not express p53 [39, 40] and THP-1 cells expressed mutant inactive p53, thus lacking functional p53 [41, 42].…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6] Over the last 2 decades, enormous progress has been made in determining recurrent cytogenetic and molecular abnormalities in AML and their prognostic implications. For patients with cytogenetically normal AML, the prognosis can be refined by the mutational status of the genes nucleophosmin (NPM1), [7][8][9] fms-related tyrosine kinase 3 (FLT3), [10][11][12] and CCAAT/enhancer binding protein (C/EBP), alpha (CEBPA). 13,14 Recurrent mutations in IDH, AXL receptor tyrosine kinase (ASXL), DNMT3a, TET2, MLL, and PHF6 have recently been identified, for which the prognostic effect is being actively investigated in combination with previously described cytogenetic and molecular features.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 To gain further insight into the role of chromothripsis in AML, we performed an integrative analysis consisting of genomic profiling (Affymetrix GeneChip Human Mapping 250K Array (n=61), Genome-Wide Human SNP Array 6.0 profiling (n=51) [GEO accession number GSE 34542]) and TP53 mutation screening in 112 CK-AML patients. 5,7 The findings were correlated with clinical and genetic data of all CK-AML, whereas outcome analysis was restricted to 62 patients treated with intensive chemotherapy. In addition, global gene expression profiling (GEP) was performed in a subset of cases haematologica 2018; 103:e18 LETTERS TO THE EDITOR SNP profiling identified a total of 67 rearrangement patterns in 39 out of 112 (35%) CK-AML patients, consistent with chromothripsis defined by the presence of at least ten switches between two or three copy-number states on an individual chromosome.…”
mentioning
confidence: 99%